The role of weak interactions in characterizing peptide folding preferences using a QTAIM interpretation of the Ramachandran plot (ϕ‐ψ). Issue 2 (17th August 2017) - Momen, Roya; Azizi, Alireza; Wang, Lingling; Yang, Ping; Xu, Tianlv; Kirk, Steven R.; Li, Wenxuan; Manzhos, Sergei; Jenkins, Samantha
Abstract: The original Ramachandran plot is a potent way to understand structures of biomolecules, however only backbone conformations are considered. We formulate a new interpretation of the original Ramachandran plot ( ϕ‐ψ ) that can include a description of the weaker interactions including both the hydrogen bonds and HH bonds as a new way to derive insights into the phenomenon of peptide folding. Specifically, we show that QTAIM analysis permits identifying key regions of the Ramachandran plot without the need for massive data sets. The QTAIM interpreted Ramachandran plot is derived from QTAIM eigenvectors and not a trivial coordinate transformation. An investigation of both the backbone and the weaker bonds within the framework of the QTAIM interpreted Ramachandran plot was found to be in line with physical intuition. The least‐preferred directions calculated for the hydrogen bonds and HH bonds were found to coincide with the "unlikely" regions of the Ramachandran plot. Abstract : The Ramachandran plot is a potent way to understand structures of biomolecules, however, their original formulation only considers backbone conformations. A new interpretation of the original Ramachandran plot (ϕ‐ψ), using quantum theory of atoms in molecules, that includes a description of the weaker interactions (like H‐bonds and H…H bonds) is introduced as a new tool to derive insights into the phenomenon of peptide folding.